Analysis of Scribbling Activities as Self-Expression and Creativity in Early Childhood - Wilda Fitria Nurliani; Asep Kurnia Jayadinata; Dhea Ardiyanti (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Ilmu Pendidikan, Universitas Negeri Makassar, 2026)
This study aims to analyze scribbling activities as a medium of self-expression and creativity in early childhood. The study is based on the view that children’s scribbles are often perceived merely as random marks or fine motor exercises, although they may contain symbolic meanings related to emotions, experiences, and imagination. Using a qualitative case study approach, this investigation was conducted at one of the early childhood education units in Purwakarta. Data were collected through observation, interviews, and documentation of children’s visual works. The findings show that scribbling goes beyond ordinary physical-motor activity; it functions as symbolic representation that communicates feelings, daily memories, and children’s imagination. Children who are given the freedom to scribble tend to show creativity, flexibility in thinking, and confidence in expressing ideas. Environmental factors, especially teachers and the learning environment, play an important role in facilitating children’s expressive and creative development. This study concludes that scribbling should be positioned as a meaningful learning activity that supports children’s holistic development.